Tabish Khair’s Just Another Jihadi Jane: Western Civilization and ‘War on Terror’ Versus Islamist Terrorism as the Two Sides of the Globalization Coin - Dolores Herrero (Societies, 2018)
Armed conflicts and violence have always been concomitant with human history but it is undeniable that our perception of them has undergone some disturbing evolution of late. Whereas in the past wars and organized violence were mainly regarded as being temporary, that is, originating in a number of reasons and tensions that might become eventually solved and confined to very specific zones on the world map, nowadays most people feel that nobody can escape the scourge of indiscriminate violence and this is mainly due to terrorism, in particular to that associated with Muslim fundamentalism. The aim of this paper will be to discuss the origins of this form of terrorism, together with its inextricable relationship with the so-called ‘civilized’ West, putting the emphasis on its more secular aspects and implications so as to show how Tabish Khair’s novel, Just Another Jihadi Jane denounces the effects that this conflict can have upon average people, all the more so if they happen to be Muslim women living in the western world.